About trade unions - Kadirova Mamlakat; Mominovna (Genius Journals, 2023)
This article presents opinions on the activities, rights, duties, and obligations of trade unions. Also, comments on the law on trade unions established in Uzbekistan, the tasks and goals of this law are highlighted
Keywords: citizen; voluntariness; department of trade unions; charter